Survival Outcomes and Pattern of Relapse After SABR for Oligometastatic Prostate Cancer - Mercier, Carole; Claessens, Marc; De Troyer, Bart; Debacker, Tibaut; Fransis, Karen; Vandeursen, Hendrik; Ost, Piet; Dirix, Piet (Frontiers in Oncology, 2022)
Introduction The addition of stereotactic ablative radiotherapy (SABR) to standard of care for patients with oligometastatic prostate cancer has the potential of improving survival and delaying further metastases. The primary aim of this analysis is to report survival outcomes and pattern of recurrence of patients with hormone-sensitive (HSPC) and castrate-resistant (CRPC) oligometastatic prostate cancer treated with SABR. Methods This is a single-center retrospective study of patients with oligometastatic prostate cancer treated in Iridium Network between 2014 and 2018. All patients with oligometastatic (≤3 active lesions) HSPC and CRPC treated with SABR were included. Data were collected using electronic records. Patterns of first progression following SABR were reported. Kaplan-Meier methods were used to determine survival outcomes. Results Eighty-seven men received SABR to 115 metastases. Nineteen patients were castrate-resistant and 68 hormone-sensitive at the time of SABR. Median follow-up was 41.6 months. In 25% of patients, no decline from baseline PSA was recorded. Median bPFS was 11.7 months (95% CI 7.6 - 18.3) for HSPC as well as CRPC (95% CI 6.4 - 24.0) (p=0.27). Median DMFS was 21.8 (95% CI 16.9 - 43.2) versus 17.6 months (95% CI 6.7 - 26.2) for HSPC versus CRPC, respectively (p=0.018). Median OS was 72.6 months (95% CI 72.6 – not reached) for HSPC and not reached for CRPC (95% CI 35.4 months – not reached) (p=0.026). For the subgroup of oligorecurrent HSPC, short-term androgen-deprivation therapy was associated with improved bPFS (median 6.0 vs. 18.3 months, HR 0.31, p<0.001) and DMFS (median 15.8 vs 29.6 months, HR 0.5, p=0.06). Information on pattern of relapse was retrieved for 79 patients: 45% (36/79) of these patients were long-term disease-free (>18 months), 28% (22/79) of patients wmere oligoprogressive (≤3 new lesions) and 27% (21/79) developed a polymetastatic relapse. Conclusion In this cohort, oligometastatic HSPC showed potential benefit from SABR with a median DMFS of 21.8 months. Well-selected patients with oligometastatic CRPC may also benefit from SABR. For patients with metachronous and repeat oligorecurrent HSPC, combining SABR with short-term androgen-deprivation therapy was associated with improved bPFS and DMFS. Overall, 36/87 (41%) of patients were still free from clinical relapse at 18 months.